179k views
0 votes
Describe each step taken to solve the equation. Then, check the solution to see if it is valid. If it is not a valid solution, explain why a) √x+6=4b)∛x+6=4.

User Atsby
by
6.3k points

1 Answer

6 votes

Answer:

Explanation:

given,

a) √x + 6 = 4

to solve the above equation subtract both side with 6

√x + 6 - 6 = 4 - 6

√x = -2

squaring both side

(√x)² = (-2)²

x = 4

a) ∛x + 6 = 4

to solve the above equation subtract both side with 6

∛x + 6 - 6 = 4 - 6

∛x = -2

cubing both side

(√x)³ = (-2)³

x = -8

User Swietyy
by
5.8k points